The credibility of satellite news channels directed in Arabic from the perspective of Iraqi media, Survey Study - Abbas Al Obedi, Ahmed Ayad; yaseen Al Azawi, Hussein Rashid yaseen Al Azawi (ALBAHITH ALALAMI, 2018)
This research aims at identifying the commitment of satellite news channels in Arabic to the set of important standards that reflect their credibility in dealing with the media material, and considering that these channels give special importance to events in Iraq, as well as the Arab region and the world, decide to choose them and study them with a problem The research was a question about the level of credibility of Iraqi media. This research is descriptive research, which used the survey method on an objective sample of 245 items, while the questionnaire was used as a data collection tool. Seven channels were selected in Arabic for the study. The three most watched channels were chosen. These channels included the channels of Russia today and the Alhurra Iraq and the BBC Arabic to achieve the objectives of the research to identify the order of the channels directed in Arabic in terms of the size of the viewership and verify the hypothesis that there are differences A statistical indication between channels channeled in Arabic in terms of level of credibility, and reached the search to the channel of Russia today, the list of channels ranked first in terms of the size of viewership and then the BBC Arabic channel, and then came Alhurra Iraq channel, Oriented close levels, as the results showed no statistically significant differences.